Initiative and option in transition for doubling farmers’ income - Singh, Manender; Tomar, S. S.; Chaudhary, Gaurav; Tripathi, Siddharth Prakash (Indian Farming, 2018)
The Government of India has already planned to take many measures to increase farm income, stabilize production and, consequently, improve small farm productivity. Integrate farming system approach involving synergic blending of crops, horticulture, dairy, fisheries, poultry, etc. seems viable option to provide regular income and at site employment to small land holder, decreasing cultivation cost through multiple use of resources and providing much needed resilience for predicted climate change scenario. HYV and hybrid seeds are very essential for a successful crop production and increasing the yield by 15-20% depending upon the crop and it can be further raised up to 45% with efficient management of other inputs. Micro-irrigation along with the nutrient application can be highly efficient and priority should be given to empower farmers with micro irrigation. The government is aggressively promoting a new crop insurance (PMFBY) given increased challenges by farmers due to frequent climate disturbances.